HUBUNGAN UMUR DENGAN KEPATUHAN KUNJUNGAN ANTENATAL CARE (ANC) DI ERA PANDEMI COVID 19 - Hastutik, Hastutik; Noviani, Aris; Utami, Uji (Jurnal Ilmiah Maternal, 2023)
It is assumed that the decrease in ANC service coverage in 2020 occurred due to the implementation of programs in regions affected by the Covid-19 pandemic (Kesga, 2021). Apart from these factors, there are other factors that can influence pregnant women's compliance with ANC visits, one of which is age. The aim of this research is to determine the relationship between age and compliance with antenatal care (ANC) visits in the Covid-19 pandemic era. The research method used is analytical observational. The research location was carried out at PMB Ngudi Saras, Ngringo, Jaten, Karanganyar. The population of pregnant women was 460 respondents. Determining the sample using the Krejoie Table and Harry King's Nomogram obtained 210 respondents. Data analysis using chi square. The research results obtained a p result of 0.389 so the p value was > 0.05. Based on the results of statistical tests, it can be concluded that Ha is rejected and Ho is accepted so that there is no significant relationship between age and ANC compliance.